Step-by-step explanation:
the rhombus is both rectangle and square
Answer:
4 ∙ (3 ∙ 6) = (4 ∙ 3) ∙ 6
Step-by-step explanation:
The associative property of multiplication states that rearranging the parentheses in an expression will not change the result, as shown.
Is there any picture we can work with?
<em>g(x)</em> = <em>x</em>² - <em>x</em> - 6
so
<em>g</em> (-4) = (-4)² - (-4) - 6 = 16 + 4 - 6 = 14
When <em>g(x)</em> = 6, we have
6 = <em>x</em>² - <em>x</em> - 6
<em>x</em>² - <em>x</em> - 12 = 0
Solve for <em>x</em>. We factorize this easily as
(<em>x</em> - 4) (<em>x</em> + 3) = 0
which gives
<em>x</em> - 4 = 0 <u>or</u> <em>x</em> + 3 = 0
<em>x</em> = 4 <u>or</u> <em>x</em> = -3